Influência da suplementação com creatina pós-exercício excêntrico na sinalização miogênica e rendimento físico em ratos - Silveira Junior, Mauro Eduardo Porto da (2017)
Creatine (Cr) is one of the most studied compounds in sports in the world due to its proven ergogenic properties. In this context, recent studies have highlighted other effects of Cr, demonstrating a possible trophic effect on skeletal muscle, as well as the ability to minimize the inflammatory process triggered by exercise. Eccentric exercise (EE) is associated to skeletal muscle damage, leading to an exacerbated inflammatory process, which ultimately slows muscle recovery. Thus, the objective of this study was to investigate the influence of acute Cr supplementation on myogenesis signaling and exercise performance after an EE-induced muscle damage protocol. Male Wistar rats performed a downhill running exercise on a treadmill at a -16º tilt and a constant speed for 90 min (5 min/bout separated by 2 min of rest). After, the animals were divided into 4 groups: a control unexercised, CMC exercise (vehicle - 0,05%), exercise Creatine (Cr – 300mg/kg/day) and exercise Ibuprofen (IBU – 15mg/kg/day). Biochemical assays to measure Cr concentration, IGF-1 and PGE-2 content, histology, and Myf-6 and Myo-D protein content were performed in soleus muscle at 24 and 48 h after a downhill running. Additionally, an exercise performance test was performed 48 h after the EE bout. Statistical analyses revealed that while IBU was effective on reducing muscle damage, Cr group presented muscle injury but effective to increase IGF-1 levels and Myf-6 protein content after EE. Additionally, Cr group presented lower levels of PGE-2 and sustained the exercise performance 48 h after EE bout. Thus, our results suggest that Cr supplementation may influence in the processes of muscle regeneration induced after injury by an EE bout.